2019
DOI: 10.4251/wjgo.v11.i5.404
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological characteristics of needle core biopsy and surgical specimens from patients with solitary hepatocellular carcinoma or intrahepatic cholangiocarcinoma

Abstract: BACKGROUND Pathological manifestations of hepatic tumours are often associated with prognosis. Although surgical specimens (SS) can provide more information, currently, pre-treatment needle core biopsy (NCB) is increasingly showing important value in understanding the nature of liver tumors and even in diagnosis and treatment decisions. However, the concordance of the clinicopathological characteristics and immunohistochemical (IHC) staining between NCB and SS from patients with hepatic tumours we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Tumor biopsy is not routinely used because of its invasiveness and concern regarding procedure-related complications (16)(17)(18)(19). There is also the possibility of misdiagnosis due to sampling errors in percutaneous liver biopsy (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor biopsy is not routinely used because of its invasiveness and concern regarding procedure-related complications (16)(17)(18)(19). There is also the possibility of misdiagnosis due to sampling errors in percutaneous liver biopsy (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Core biopsy, as a new diagnostic method, shows great potential value in judging the character of liver tumor. Two studies confirmed the feasibility of core biopsy in the diagnosis of liver tumor through staining with tumor markers such as cytokeratin-19, glypican-3 (GPC3), hepatocyte paraffin-1, arginase-1, AFP, pCEA and CD10 (23,24). Despite continuous improvements in diagnostic and treatment methods, In our study, we first used HCCDB database to analyze the difference in NTF3 expression between liver cancer tissues and normal tissues.…”
Section: Discussionmentioning
confidence: 90%
“…A new diagnostic method called core biopsy has displayed potential value in judging the character of ICC. 33 The prognosis of ICC remains poor despite the use of highly effective diagnostic tools and treatment methods. It is urgent to find effective prognostic markers for ICC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment and prognosis of ICC is still a thorny issue. A new diagnostic method called core biopsy has displayed potential value in judging the character of ICC 33 …”
Section: Discussionmentioning
confidence: 99%